(Bill Draft on Eliminating Sexual Violence: Access to Justice, Truth and Victims’ Survival - Khusnaeny, Asma'ul (Yayasan Jurnal Perempuan, 2016)
Sexual violence is a crime against humanity, violations of human rights and gender-based violence. Meanwhile since the 1998-2013 National Commission on Violence Against Women has been monitoring and documentating 15 (fifteen) forms of sexual violences. National Commission on Violence Against Women was classifying all forms of sexual violence from 15 forms into 6 sexual violences based on common elements in criminal offense. So far the handling cases of sexual violence faced barrier to prevention, protection, recovery of victims, rehabilitation of offenders, and the criminal justice procedure of law. State should be responsible quickly to enact Law on Elimination of Sexual Violence, as part of country’s efforts in implementing the principles of due diligence.